Developments in Music Therapy Practice : Case Study Perspectives - Meadows, Anthony N. (Barcelona Publishers, 2011)
This book presents 34 case studies from music therapists around the world. These studies represent practices from a broad range of clinical orientations, including recent developments in the field. This includes cognitive-behavioral, humanistic, psychodynamic, medical, community, aesthetic and healing practices with infants, children, adolescents, adults and older adults. Various models of music therapy are also represented, including Guided Imagery and Music, Analytic Music Therapy, Behavioral Music Therapy and Nordoff-Robbins Music Therapy. Each chapter includes a description of the author's theoretical foundation(s), assessment process, therapeutic process and health outcomes, encompassing improvisational, receptive, recreative, compositional and creative arts methods and techniques. Conceived as a textbook for training students, this collection may also be used as an introduction to music therapy, and as a reference that reflects developments in practice within the field.